N-Substituted 5-amino-1-hydroxymethyl-cyclopentanetriols: A new family of activity promotors for a GM1-gangliosidosis related human lysosomal β-galactosidase mutant. (18th April 2017) - Schalli, Michael; Tysoe, Christina; Fischer, Roland; Pabst, Bettina M.; Thonhofer, Martin; Paschke, Eduard; Rappitsch, Tanja; Stütz, Arnold E.; Tschernutter, Marion; Windischhofer, Werner; Withers, Stephen G.
Abstract: From 1, 2;3, 4-di- O -isopropylidene-α-D-galactopyranose, a series of highly functionalized (hydroxymethyl)cyclopentanes was easily available. In line with reports by Reymond and Jäger on similar structures, these amine containing basic carbasugars are potent inhibitors of β-D-galactosidases and, for the first time, could be shown to act as pharmacological chaperones for GM1 -gangliosidosis-associated lysosomal acid β-galactosidase mutant R201C, thus representing a new structural type of pharmacological chaperones for this lysosomal storage disease. Graphical abstract: Highlights: A simple, short and high yielding route enables access to amino(hydroxymethyl)pentanetriols. Additional modifications are available by simple 1- N -alkylation. Final products are potent inhibitors of a panel of β-galactosidases. New compounds are efficient pharmacological chaperones for GM1 -gangliosidosis-related lysosomal β-galactosidase.